2018
DOI: 10.2478/jlecol-2018-0011
|View full text |Cite
|
Sign up to set email alerts
|

Forests in the Czech Public Discourse

Abstract: Forests are being increasingly studied within the framework of social sciences, especially in relation to environmental problems and global climate change. This article deals with the perception of Czech forests and their management at two basic levels: at the level of sociological analysis of in-depth interviews with experts in the field of forestry and at the level of public opinion research. The main aim of this study was to describe the attitudes of professionals and the general public towards forests and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…These local findings match the results of an expert-based study across Europe, where respondents rated large, old trees as the most important forest feature but deadwood was ranked only tenth out of 12 possible positions on a scale (Edwards et al 2012). Tourists generally expressed a preference for forests without deadwood (Stachová 2018) even when they were aware of the importance of deadwood for forest biodiversity (Pelyukh et al 2019). These examples illustrate a need to increase public understanding of deadwood's importance in forests.…”
Section: Public Perception Of Deadwoodsupporting
confidence: 77%
See 1 more Smart Citation
“…These local findings match the results of an expert-based study across Europe, where respondents rated large, old trees as the most important forest feature but deadwood was ranked only tenth out of 12 possible positions on a scale (Edwards et al 2012). Tourists generally expressed a preference for forests without deadwood (Stachová 2018) even when they were aware of the importance of deadwood for forest biodiversity (Pelyukh et al 2019). These examples illustrate a need to increase public understanding of deadwood's importance in forests.…”
Section: Public Perception Of Deadwoodsupporting
confidence: 77%
“…2012). Tourists generally expressed a preference for forests without deadwood (Stachová 2018) even when they were aware of the importance of deadwood for forest biodiversity (Pelyukh et al . 2019).…”
Section: Public Perception Of Deadwoodmentioning
confidence: 99%
“…Daniel et al [105] showed that the density of deadwood affects aesthetic beauty from an ecotourism perspective for most forest goers. Other studies have shown that forests with large amounts of deadwood are unattractive to the public and are viewed as chaotic, untidy, and ruined [106][107][108][109][110]. Similarly, in Kenya, even though not as explicit as in the studies mentioned earlier, the National Biodiversity Strategy and Action Plan for 2019-2030 identifies negative attitude and complex cultural factors among the key issues hindering biodiversity conservation and which could be extrapolated to deadwood management as well.…”
Section: Discussionmentioning
confidence: 93%
“…Studies have shown that the aesthetic beauty of a landscape is affected by the density and diversity of trees, including deadwood [105], which attracts people to visit forests. Unfortunately, forests with large amounts of deadwood are viewed as chaotic, untidy, and destroyed [88,[106][107][108][109][110]. However, Pastorella et al [111] showed that the preferred type of forests related to different management forms of deadwood (unmanaged forests, closeto-nature forests, extensively managed forests, and intensively managed forests).…”
mentioning
confidence: 99%
“…Nowadays, 34% of the Czech Republic area is covered by woodland of which most of the area is occupied by commercial forests [1]. Commercial forests are managed by different types of harvesting practices.…”
Section: Introductionmentioning
confidence: 99%